The influence of perceived safety culture and safety knowledge on safety performance mediated by safety motivation: Study of field work partner employees at PT. PLN (Persero) Central Kalimantan Distribution Main Unit - Karina, Alda; Ariffin, Zakhyadi (International research journal of management, IT and social sciences, 2024)
Perceived safety culture and safety knowledge are the two independent variables in this study. Safety performance is the dependent variable, and safety motivation is the mediating variable at PT. Central Kalimantan Distribution Main Unit of PLN (Persero). This research method uses a questionnaire with 101 employees of fieldwork partners at PT. PLN (Persero) Central Kalimantan Main Distribution Unit is the sample and has been selected from the population. Variable estimations utilize the LC procedure with a weight scale from 1 to 5. Utilize the partial least squares method to determine the correlation between variables X1, X2, Y, and Z. The consequences of the examination express that (1) PSC meaningfully affects SP, (2) SK affects SP, (3) SM affects SP, (4) PSC affects SM, (5) SK significantly affects SM, (6) PSC affects SP with SM Intercession and (7) SK affects SP with SM Intervention.